HUBUNGAN DUKUNGAN SOSIAL KELUARGA DENGAN PSYCHOLOGICAL WELL-BEING PADA NARAPIDANA ANAK DI LAPAS KLAS 1 KUTOARJO - Yehezkiel Adi Nugroho (Jurnal Basicedu, 2020)
The research aims to knowing the relationship between social support and psychological well-being in child prisoner. This research is designed by using sampling saturated technique with 53 participants. Variable of family social support using Cutrona’s theory (1987) which consist of 24 items and psychological well-being variable using Ryff’s theory (1989) which consists of 42 items. The research method in data collecyion using scale method. That is the scale of family social support and the Ryff’s psychological well-being scale. Data analysis using the product moment correlation analysis techniques and obtained a comparison coefficient of 0,688 with a sig value.= 0,000 (p< 0,001). Based on the research result shows a positive relationship between family social support and psychological well-being on child prisoner in prison in kutoarjo.